Combinational Effect of Rumex tingitanus (Polygonaceae) Hexane Extract and Bacillus thuringiensis δ-Endotoxin against Spodoptera littoralis (Lepidoptera: Noctuidae). (8th August 2018) - Mhalla, Dhekra; Ben Farhat-Touzri, Dalel; Tounsi, Slim; Trigui, Mohamed
Abstract : The increasing insect resistance against Bacillus thuringiensis delta-endotoxins is a serious problem which makes it urgent to look for new eco-friendly strategies. Combining these toxins with other biomolecules is one of the promising strategies against insect pests. In this work, we evaluated the bioinsecticidal potential of Rumex tingitanus extracts and B. thuringiensis strain BLB250 against Spodoptera littoralis (Lepidoptera: Noctuidae) larvae. The chemical composition of the hexane extract, the most active fraction, was analyzed to validate the correlation between chemical composition and biological activity. Among the tested extracts, only the hexanic extract showed toxicity against first and second instar larvae with LC50 of 2.56 and 2.95 mg g −1, respectively. The Bacillus thuringiensis BLB250 delta-endotoxins showed toxicity with an LC50 of 56.3  μ g g −1 . Therefore, the investigated combinational effect of BLB250 delta-endotoxins and R. tingitanus hexane extract proved significant synergistic effect against S. littoralis larvae . The GC-MS analysis of R. tingitanus hexane extract showed the richness of this extract in phytosterols such as β andγ - sitosterol (48.91%), campesterol (6.43%), and β -amyrin (8.92%) which are known for their insecticidal activity. This novel finding highlights the potential use of this combination against insect pests to prevent the appearance of resistance problems.